PENDAMPINGAN PENERAPAN GOOD MANUFACTURING PRACTISE (GMP) PADA UMKM KERIPIK TEMPE 27, GENTAWANGI, JATILAWANG, BANYUMAS - Wijayanti, Nur; Budhi Pramono, Taufik; Dharmawan, Budi (Politeknik Negeri Lampung, 2022)
ABSTRACT Tempe 27 chips are a product of partner Micro, Small and Medium Enterprises (SME) from Gentawangi Village, RT 02 RW 06, Jatilawang sub-district, Banyumas district. The type of tempe chips produced by partner SME is sago tempe chips. The problems faced by partner SME include that the production equipment used is still simple and has not yet implemented Good Processed Food Production Methods (CPPOB) or Good Manufacturing Practices (GMP). The solutions offered to partner SME are public education and the diffusion of science and technology through training and mentoring in the application of Good Manufacturing Practice (GMP). The aim is to increase the knowledge, skills and awareness of SME to reach 100% regarding the implementation of GMP. The methods used are community education, science and technology diffusion, mediation, advocacy and participation from SME partner in community service activities. The result of the community service program related to assisting in the implementation of GMP is that there is an increase in understanding and awareness of the importance of GMP from partner SME actors. This is shown by the high motivation of partner SME and their willingness to independently improve, equip and organize tempe chip production facilities and infrastructure so that they comply with GMP principles. Keywords: GMP, tempe chips, mentoring, SME